(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This paper on History and Aesthetics of Stage Lighting aims to describe and analyze, through case studies, the practice and theory of Richard Wagner, Adolphe Appia, Edward Gordon Craig, Georg Fuchs and Max Reinhardt about staging, from the point of view of Scene Lighting and its spatial relationships, proposing a turning point in the idea and use of the scenic space, based on a revolution in the use of electric light and its functions in the show at the turn of the 20th century. Thus, the Stage Lighting language becomes, from there on, a fundamental tool of interplay between time and space, edition and dramaturgy of the visible in modern staging. Keywords: History and Aesthetics of Stage Lighting. Scenic Space. Adolphe Appia. Edward Gordon Craig. Max Reinhardt.